Analysis of Rural Industrial Integration on Rural Revitalization: Impact Mechanism and Spatial Effect - Zhang, Yaoyuan (Journal of Global Economy, Business and Finance, 2025)
Rural industrial integration is a key path to promote the rural revitalization strategy. Based on panel data from 29 provinces in China from 2010 to 2022, this study constructs a comprehensive evaluation index system for rural revitalization and industrial integration. The entropy method, AHP method and entropy weight TOPSIS method are used to measure the development level of the two. The influencing mechanism is explored through OLS regression, mechanism test, robustness, heterogeneity analysis and spatial model. The study found that: (1) The level of rural revitalization and industrial integration is on an upward trend overall, but there are significant regional differences, showing a “high in the east and low in the west” pattern. The eastern region takes the lead with its policy first-mover advantage and industrial cluster effect, while the central and western regions are lagging behind due to factors such as weak infrastructure and a single industrial chain. (2) Industrial integration has a significant positive role in promoting rural revitalization by increasing farmers’ income and promoting industrial structure upgrading, and there is a spatial spillover effect, indicating that industrial integration in a province can drive the development of neighboring provinces through economic linkage. (3) Regional heterogeneity analysis shows that the marginal benefits of industrial integration in the eastern region are higher, while the benefits of integration in the central and western regions have not yet been fully released due to poor factor flow and insufficient policy adaptability. The study further indicates that digital technology empowerment, industrial chain extension, and ecological and economic synergy are the core pathways for industrial integration to drive rural revitalization. By constructing a multidimensional indicator system and analyzing spatial effects, this paper demonstrates that the degree of industrial integration positively impacts rural revitalization, providing theoretical and empirical support for optimizing regional policies and addressing development imbalances.